Research on design method of manoeuvring targets tracking generator based on LabVIEW programming. (24th December 2021) - Gao, Caiyun; Wang, Shiqiang; Zeng, Huiyong; Bai, Juan; Zong, Binfeng; Cai, Jiliang
Aiming at the issue of poor visual display and non-real time status output while describing manoeuvring target track with data, a new design method of target track generator is proposed based on laboratory virtual instrument engineering workbench (LabVIEW). Firstly, the motion model of manoeuvring target is built. Secondly, the design requirement of track generator is discussed. Finally, target track of multiple targets and multiple manoeuvring model is produced by visual panel and code design with LabVIEW. Simulation results indicate that the proposed method can output the target status in real time with different data rates while displaying the multiple targets manoeuvring track directly and have good visibility. And also the generated track parameters are of high accuracy and effective data.